All‐cellulose composites prepared by partially dissolving cellulose using NaOH/thiourea aqueous solution. Issue 48 (23rd July 2021) - Hu, Fuqiang; Wang, Miaolin; Wang, Na; Hu, Yucheng; Gan, Meixue; Liu, Danqing; Xie, Yimin; Feng, Qinghua
Abstract: All‐cellulose composites (ACCs) were prepared by partially dissolving cellulose in the filter paper using NaOH/thiourea aqueous solution. The effects of dissolution time, thiourea ratio, and temperature on the properties of ACCs were investigated. ACCs were characterized by scanning electron microscope, attenuated total reflectance Fourier transform infrared spectroscopy, Raman spectroscopy, X‐ray diffraction, and tensile tests. The results revealed that the fibers in ACCs were tightly intertwined. The crystalline form of cellulose in ACCs was transformed from type I to type I/II mixture, and the crystallinity decreased from 77.32 to 51.40%. The tensile strength of ACCs was remarkably improved to 23.16 MPa. The results confirmed ACCs had a high potential for practical applications in the packaging field. Abstract :